Intraductal Papillary Mucinous Neoplasm of the Pancreas: An Overview of Surgical Management - Kasakewitch, João Pedro Gonçalves; Filardi, Kaique Flavio Xavier Cardoso; Fligor, Scott C.; Kent, Tara Sotsky (Digestive Disease Interventions, 2025)
Intraductal papillary mucinous neoplasms (IPMNs) are commonly identified cystic lesions in the pancreas that may carry malignant potential for pancreatic ductal adenocarcinoma. Risk stratification of identified lesions is critical to determine which patients may benefit from surgical resection. Key high-risk features include size, growth, main pancreatic duct involvement, obstructive jaundice, and enhancing solid components on imaging. The surgical technique of choice depends on IPMN location, with pancreatoduodenectomy being the most common procedure due to the high incidence of high-risk IPMNs in the head of the pancreas. The extent of resection is guided by imaging and/or endoscopic data, potentially including intraoperative frozen section analysis to assess for high-grade dysplasia or invasive IPMN. Postoperative surveillance of the remnant gland is crucial and based on the risk of disease recurrence after the surgery, which is determined by the anatomopathological report.
Keywords: pancreatic cystic neoplasms; pancreatic cancer; intraductal papillary mucinous neoplasm; pancreatic adenocarcinoma; pancreatic surgery